Annual Plan 2005-2006 (Volume-VI) Physical Targets/Achievements National Capital Territory of Delhi - Planning Commission (Planning Commission, 2005)
Agriculture and Allied Services, Rural Development, Energy, Industries, Transport, Science Technology and Environment, Tourism, General Education, Technical Education, Art and Culture, Medical, Water Supply and Sanitation, Housing, Urban Development, Information and Publicity, Welfare of SC/ST/OBC, Labour and Labour Welfare, Social Welfare, Nutrition, Public Works.
Planning Department, Government of National Capital Territory of Delhi